IMPLEMENTATION OF THE VIDEO-ASSISTED SIMULATION-BASED LEARNING MODEL ON THE PROCLAMATION OF INDONESIAN INDEPENDENCE MATERIAL: Penerapan Model Pembelajaran Simulation Based Learning Berbantu Video Pada Materi Proklamasi Kemerdekaan Indonesia - Juliandry Kurniawan Junaidi; Kaksim; enjelia Maratua (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the application of the video-assisted Simulation-Based Learning (SBL) model to enhance student engagement and understanding of the Proclamation of Indonesian Independence. The background of this research is based on the lack of variety in teaching methods used by teachers, which often results in student passivity in the learning process. The study employed a descriptive qualitative approach which aims to provide an in-depth description of the process and impact of implementing this learning model. The research was conducted at SMA Negeri 4 Sijunjung with grade XI F2 students in the even semester of the 2024/2025 academic year. In line with the characteristics of qualitative research, data collection was carried out through classroom observation to capture student activities and teacher–student interactions during the implementation of the SBL model, in-depth interviews with the history teacher and several students as key informants to explore their perceptions, experiences, and responses, as well as documentation in the form of photographs, video recordings of learning activities, and supporting documents such as lesson plans (RPP). The results showed that the integration of the SBL model with video media significantly increased student learning motivation, critical thinking skills, and understanding of the historical context. Students were actively involved in role-playing simulations that reconstructed the events of the proclamation of independence, enabling them to connect emotionally and cognitively with the historical event. This research confirms that the combination of SBL and audiovisual media is a contextual and engaging history learning strategy that positively impacts students’ motivation, participation, and comprehension.